1997
DOI: 10.1302/0301-620x.79b5.0790764
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Myelography in Brachial Plexus Injury

Abstract: We used magnetic resonance (MR) myelography in ten patients with injuries to the brachial plexus and compared the findings with those obtained by conventional myelography and postmyelographic CT (CTM). In the presence of complete nerve-root avulsion (seven cases), a post-traumatic meningocele was detected by MR myelography. In injuries to the upper roots (three cases) MR myelography showed abnormal findings with a high signal intensity in the nerve root, obliteration of the damaged nerve root, or enlargement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 21 publications
0
25
0
3
Order By: Relevance
“…Although CT-myelography is still considered to be the "gold standard" for studying root lesions, recent advances in magnetic resonance imaging (MRI) are producing images of much higher resolution, such that MRI can now match the diagnostic accuracy of CT-myelography 35,36 . Because of continuous development of MRI techniques, this imaging examination will soon become the most important method for evaluating brachial plexus injuries.…”
Section: Electrophysiological and Imaging Evaluationsmentioning
confidence: 99%
“…Although CT-myelography is still considered to be the "gold standard" for studying root lesions, recent advances in magnetic resonance imaging (MRI) are producing images of much higher resolution, such that MRI can now match the diagnostic accuracy of CT-myelography 35,36 . Because of continuous development of MRI techniques, this imaging examination will soon become the most important method for evaluating brachial plexus injuries.…”
Section: Electrophysiological and Imaging Evaluationsmentioning
confidence: 99%
“…In fact, MR imaging is claimed to be the technique of choice for most brachial plexus pathologic conditions by several authors ( 5,(18)(19)(20). However, few MR studies in OBPLs and adult brachial traumatic plexopathies have actually reported observation of the roots from the spinal cord by using three-dimensional T2-weighted sequences (21)(22)(23). Most of these reports focused only on the presence of pseudocysts ( 11,(24)(25)(26)(27).…”
Section: Neuroradiology: Ct Myelography In Obstetric Brachial Plexus mentioning
confidence: 99%
“…MRI has improved over the past several years and can be helpful in evaluating the patient with a suspected nerve root avulsion [24][25][26]. It has some advantages over CT/myelogram because it is noninvasive and can visualize much of the brachial plexus, whereas CT/myelography shows only nerve root injury.…”
Section: Radiographic Evaluationmentioning
confidence: 99%